Maize BIG GRAIN1 homolog overexpression increases maize grain yield - Simmons, Carl R. (Plant Biotechnol J, 2020)
The Zea Mays BIG GRAIN 1 HOMOLOG 1 (ZM‐BG1H1) was ectopically expressed in maize. Elite commercial hybrid germplasm was yield tested in diverse field environment locations representing commercial models. Yield was measured in 101 tests across all 4 events, 26 locations over 2 years, for an average yield gain of 355 kg/ha (5.65 bu/ac) above control, with 83% tests broadly showing yield gains (range +2272 kg/ha to −1240 kg/ha), with seven tests gaining more than one metric ton per hectare. Plant and ear height were slightly elevated, and ear and tassel flowering time were delayed one day, but ASI was unchanged, and these traits did not correlate to yield gain. ZM‐BG1H1 overexpression is associated with increased ear kernel row number and total ear kernel number and mass, but individual kernels trended slightly smaller and less dense. The ZM‐BG1H1 protein is detected in the plasma membrane like rice OS‐BG1. Five predominant native ZM‐BG1H1 alleles exhibit little structural and expression variation compared to the large increased expression conferred by these ectopic alleles.